Laboratory manual for human biology - Morton, David; Perry, James W.; Perry, Joy B. 1952- (Brooks/Cole, 2012)
This lab manual includes inquiry-based experiments, relevant activities, and supporting questions that assess recall, understanding, and application. Each of the 21 exercises guides students through objectives, introduction, materials, procedure, pre-lab questions and post-lab questions.--